A molecular dynamics-based analysis of the influence of strain-rate and temperature on the mechanical strength of PPTA crystallites. (27th October 2017) - Mercer, Brian; Zywicz, Edward; Papadopoulos, Panayiotis
Abstract: Molecular dynamic simulations are used to quantify how the mechanical behavior of PPTA crystallites, the fundamental building blocks of aramid fibers such as Kevlar ®, depend on strain-rate, temperature, and crystallite size. The (axial) crystallite elastic modulus is found to be independent of strain-rate and decreases with increasing temperature. The crystallite failure strain increases with increasing strain rate and decreases with increasing temperature and crystallite size. These observations are consistent with crystallite failure being driven by stress-assisted thermal fluctuations of bonds within PPTA crystallites and the concepts of the kinetic theory of fracture. Appealing to reliability theory, a model is proposed that predicts the onset of both primary and secondary bond failure within a crystallite as of function of strain rate, temperature, and crystallite size. The model is parameterized using bond failure data from constant strain-rate molecular dynamic strain-to-failure simulations and is used to compute the activation volume, activation energy, and frequency for both primary and secondary bond ruptures. Graphical abstract: Highlights: Molecular dynamics strain-to-failure simulations of PPTA crystallites are performed. Crystallite failure strain increases with increasing strain rate. Crystallite failure strain decreases with increasing temperature. Chemical kinetics is shown to explain the behavior. A model for predicting failure using reliability theory is proposed.